Stem cell models of primary tauopathies reveal defects in synaptic function. (December 2021) - Martinez, Rita; Jiang, Shan; Marsh, Jacob; Harari, Oscar; Cruchaga, Carlos; Goate, Alison M.; Temple, Sally; Karch, Celeste M.; ,
Abstract: Background: Primary tauopathies are characterized neuropathologically by inclusions containing abnormal forms of the microtubule‐associated protein tau (MAPT) and clinically by diverse neuropsychiatric, cognitive, and motor impairments. Autosomal dominant mutations in the MAPT gene cause heterogeneous forms of frontotemporal lobar degeneration with tauopathy (FTLD‐Tau). Common and rare variants in the MAPT gene increase the risk for sporadic FTLD‐Tau, including progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD). Method: We generated a collection of fibroblasts from 140 MAPT mutation/risk variant carriers, PSP, CBD, and cognitively normal controls; 31 induced pluripotent stem cell (iPSC) lines from MAPT mutation carriers, non‐carrier family members, and autopsy‐confirmed PSP patients; 33 genome engineered iPSCs that were corrected or mutagenized; and forebrain neural progenitor cells (NPCs). Result: To begin to identify the genes and pathways that are dysregulated in primary tauopathies, we performed transcriptomic analyses in induced pluripotent stem cell (iPSC)–derived neurons carrying MAPT p.R406W and CRISPR/Cas9‐corrected isogenic controls. We found that the expression of the MAPT p.R406W mutation was sufficient to create a significantly different transcriptomic profile compared with that of the isogeneic controls and to cause the differential expression of 328 genes. Sixty‐one of these genes were also differentially expressed between MAPT p.R406W carriers and control brains. Twelve of these genes are also differentially expressed between PSP and control brains. Together, these genes are enriched for pathways involved in GABA‐mediated signaling and synaptic function, which may contribute to the pathogenesis of FTLD‐tau and other primary tauopathies. Conclusion: Here, we present a resource of fibroblasts, iPSCs, and NPCs with comprehensive clinical histories that can be accessed by the scientific community for disease modeling and development of novel therapeutics for tauopathies.